Vitamin A attenuates PFOS-induced neurotoxicity and alters early proximity patterns to conspecifics in zebrafish larvae - Jiang, Peiyun; Wang, Jingyu; Wang, Xiaoying; Zou, Li; Wu, Di; Xu, Qu; Jiang, Yue; Yao, Mengmeng; Hong, Qin; Chi, Xia (Frontiers in Behavioral Neuroscience, 2025)
IntroductionPerfluorooctane sulfonic acid (PFOS), a persistent perfluoroalkyl substance with ubiquitous environmental distribution and bioaccumulative potential, has raised significant public health concerns due to its association with neurodevelopmental disorders. This study investigates vitamin A’s neuroprotective capacity against PFOS-induced toxicity, particularly focusing on social behavior deficits—a core phenotype of autism spectrum disorder (ASD).MethodsZebrafish larvae were exposed to 1 μM or 5 μM PFOS (with/without 5 nM vitamin A co-treatment) from 24–144 hours post-fertilization (hpf). Control groups received 0.01% DMSO (vehicle) or 5 nM vitamin A alone. Developmental parameters (body length, heart rate), locomotor activity (total distance moved), and neurobehavioral endpoints (conspecific interaction) were quantified using automated tracking systems (ViewPoint ZebraLab). Neurochemical alterations were assessed through qPCR (dopaminergic genes) and AO staining (apoptosis).ResultsPFOS exposure (5 μM) significantly increased inter-individual distance (IID) and reduced physical contact frequency during social interaction tests. Neurochemical analyses revealed concurrent dopamine transporter downregulation and apoptosis-related gene activation . Vitamin A co-treatment attenuated these effects.DiscussionOur findings demonstrate that PFOS disrupts early social neurodevelopment through dopaminergic dysregulation and apoptotic signaling, while vitamin A exhibits counteractive potential. this study elucidates the impact of PFOS exposure on zebrafish social behavior and brain development. while highlighting the neuroprotective potential of vitamin A against PFOS exposure, These findings have significant guiding implications for the development of public health policy and provide a scientific foundation for comprehending the neurotoxicity of PFOS and developing effective intervention measures.